Dialogue with Tradition in Historical Advertising Discourse. Polite Forms of Address - Pałka, Patrycja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The aim of the article is to present how in historical advertisement discourse the sender (the advertiser) expressed an attitude towards the recipient in the context of tradition of that time related to the principles of language politeness. In the analysis, the author focuses on describing the forms of address used. The research encompasses a period spanning from the second half of 19th century to 1939, a period directly connected with the development of professional advertisements, the advertising industry, the first advertising agencies and the media – press, radio and cinematography. The sources used to write this paper include a wide variety of materials that comprise a large collection of texts representing various forms of advertisement, including press adverts, leaflets, postcards, posters, placards and notices, packaging materials, labels, folders, company catalogues and information brochures, price lists, company paper products (forms, envelopes, notes, and bills), and other promotional printed materials (e. g. invitations, letters, and thematic cook books), as well as radio advertisements. The analysis shows both that polite communication practices in historical advertising texts are characterised by a tendency to conform to traditional language politeness norms, including those specific to trade, and that the emergence of new communication tools and the democratisation of social life during the interwar period led to a need to simplify language etiquette and trade politeness norms, as well as to develop more familiar ways of addressing the audience in advertising discourse.